Bending influence of the electrocaloric effect in a ferroelectric/paraelectric bilayer system. (14th January 2016) - Li, Y; Lin, S P; Wang, Y J; Ma, D C; Wang, Biao
Abstract: The influence of bending behavior on the electricaloric (EC) effect is investigated by adopting a thermodynamic model of ferroelectric (FE)/paraelectric (PE) bilayer. The polarization transitions driven by the bending effect occur at a certain temperature range, glass-like transitions, which are found to dramatically impact the EC response. A large range of EC response can be obtained from the FE/PE bilayer which is attributed to the varying misfit strain across the film thickness arising from the bending effect. The results suggest that careful choice of thickness ratio between FE and PE layers allows one to harness the intrinsic and extrinsic contributions to obtain the optimized EC response, which presents great potential for solid refrigeration application.